Dysbaric osteonecrosis in diving fisherman: a case report - Kurtul, Seher; Güngördü, Nejdiye (La Medicina del Lavoro, 2022)
Background: Dysbaric osteonecrosis (DON) is defined as avascular bone necrosis, usually involving specific parts of the long bones, which is seen in divers or compressed-air workers due to exposure to pressure. We describe a case of DON in an artisanal diving fisherman working underwater for many years. Methods: A 48-year-old male case was admitted to the occupational disease outpatient with left shoulder and arm pain for 1-2 years. Since the age of 20, he has been artisanal diving fishing with a hookah at a depth of 20-25 meters in the sea. In 2011, he received hyperbaric oxygen therapy for widespread pain in the whole body due to decompression sickness (DCS). In the case’s left shoulder joint x-ray and magnetic resonance imaging, degenerative changes in the acromioclavicular joint and signal changes consistent with osteonecrosis starting from the subcortical area of the humeral head and extending to the proximal shaft of the humerus were observed. Conclusions: DON is among the most common long-term pathologies in professional divers. In Turkey, as in our case, not applying safe decompression procedures and unsafe diving practices are common among diving fishers. In studies, the frequency of exposure to pressure, duration and depth of dive, insufficient decompression, formation of DCS and increasing age were associated with DON. Today, DON remains an occupational hazard with significant medical and social consequences. Diving fishers should be informed about the sequelae of DCS and trained on the safety measures to be taken.